Climate Harms. (20th December 2018) - Cullity, Garrett
Abstract: How should we think of the relationship between the climate harms that people will suffer in the future and our current emissions activity? Who does the harming, and what are the moral implications? One way to address these questions appeals to facts about the expected harm associated with one's own individual energy-consuming activity, and argues that it is morally wrong not to offset one's own personal carbon emissions. The first half of the article questions the strength of this argument. The second half maintains that a different kind of argument for the same conclusion is stronger. This focuses on the harms that are attributable to carbon emitters considered collectively.